Effects of various fat sources on growth performance of finishing pigs - David A Nichols; Robert D Goodband; Robert H Hines; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1989)
One hundred and twenty-eight finishing pigs averaging 124 lb were utilized to evaluate the effects of different fat sources on growth performance. Pigs were fed one of four diets containing either no added fat (control) or 4% added fat from soybean oil, coconut oil, or choice white grease. The control diet was formulated to contain 14.5 % crude protein and .66 % lysine. All fat-added diets were formulated with the same calorie:lysine ratio as the control diet. There were no differences in average daily gain between pigs fed either the control diet or diets containing added fat. Daily feed intake was reduced for pigs fed added fat from 4 to 7% compared to pigs fed no added fat, with pigs fed choice white grease having the lowest feed intake. This resulted in pigs fed choice white grease having 11% better feed efficiency compared to pigs fed no added fat. Pigs fed soybean oil exhibited a 4% improvement in feed efficiency, and those fed coconut oil were intermediate, with an 8% improvement in feed efficiency. These results indicate that 4% added fat reduces feed intake and improves feed efficiency of finishing pigs. In addition, it appears that choice white grease may be a superior fat source in finishing pig diets.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Finishing pigs; Soybean oil; Coconut oil; Choice white grease; Performance